За стипендію варто поборотися! - Ломейко, Олександр Петрович; Ломейко, Александр Петрович; Lomeiko, Oleksandr (My University, 2013)
Студенти ТДАТУ отримали академічні стипендії Президента України.
Keywords: ТДАТУ; Агротаврія